Penerapan Model Contextual Teaching Learning Dalam Pembelajaran Manfaat Energi Matahari Pada Tumbuhan Secara Daring Siswa Kelas IV - Pertiwi, Megantari; Wuryastuti, Sri; Suratno, Tatang (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Based on the result of observations made by researchers that during online learning, there are several obstacles in the process, such as the difficulties faced by teachers in delivering learning materials to students, especially in science learning which contained student interactions with their environment. Online learning causes students to have less learning experience, because of the limitations of teachers in providing learning, so that teachers only use worksheets as learning resources and media for students to do assignments in the form of questions that have been provided. For this reason, researchers tried to apply an online Contextual Teaching Learning (CTL) model with natural science material on the effect of solar energy on plants in theme 2 sub-theme 1. The research method used in this study is a native inquiry which will later become a narrative that contains data on the findings obtained by the researcher. The subject of this research is a study group 2 of IV grade students at SDN Banjarwangi 01 totaling 11 students. The instruments used are interviews, observations, transcripts of recordings, and field notes. The results of this study indicate that the application of the Contextual Teaching Learning (CTL) model allows it to be applied to science learning as an effort to make students continue to have their learning experiences in this online learning period and students can construct what they find. so that it makes students understand more about the material being studied, not only relying on working on worksheets. In addition, applying CTL during online learning can make students more active and increase students' enthusiasm for learning